Intraparotid metastatic papillary carcinoma (Indian Journal of Case Reports, 2025)
Intraparotid metastasis from papillary thyroid carcinoma (PTC) is an exceptionally rare occurrence, posing significant diagnostic and therapeutic challenges. This case report discusses a 41-year-old female presenting with a hard, fixed mass in the left parotid region, diagnosed as metastatic PTC, over a decade after thyroidectomy and radioactive iodine (RAI) therapy. Through clinical examination, imaging, and histopathological analysis, the diagnosis was confirmed. The patient underwent surgical intervention, followed by adjuvant therapy. This case highlights the importance of sustained surveillance in thyroid cancer patients and emphasizes the need for multidisciplinary management strategies to optimize outcomes.